PENGABDIAN MASYARAKAT TERPADU UNTUK OPTIMALISASI PRODUKSI GULA JAWA DENGAN CETAKAN ERGONOMI DI DUSUN TEMPURSARI 2 - Widyanto, R Arri; Dewangga, Eki; Istianto, Tri Anggoro; Hidayat, Arif Nur; Andrean, Bambang; Afandi, Faris (GERVASI: Jurnal Pengabdian kepada Masyarakat, 2020)
Tempursari 2 Hamlet, Tempursari Village, Candimulyo Sub-district, Magelang District, has a population of 340 people consisting of 90 family head. The main livelihoods of the residents of the hamlet are farmers. In addition, every household has a business to make Javanese caves. The potential of available raw materials is abundant, the market potential is wide open, the selling price is around Rp. 14,000-Rp. 16,000. Problems that occur in production standards and standards for the resulting palm sugar products are not the same, as is the quality. Small production capacity while large needs. The product does not yet have a good packaging, there is no good marketing technique as well, the price is controlled by the middleman because it does not yet have a Joint Business Group (KUB). The methods used in solving this problem are: Planning, Implementation and Reporting. The results achieved from this activity were: the creation of an ergonomic and standard Javanese sugar mold, a KUB of Javanese sugar-crafted KUB, a package made from woven bamboo with a label containing the KUB identity so that this Javanese sugar product could be made a souvenir by Tempursari.